Slogovna razmerja Kosovelove lirike v luči modernističnih poskusov iz zadnje ustvarjalne etape - Turk, Boštjan Marko (Slavistična revija, 1996)
The paper attempts to show the conception of Kosovel's early lyric poetry in the expressionistic tradition, and based on that, to refute the impressionism as its possible inspirational model. Proceeding from the expressionistic metaphysic of Kosovel's early texts, it argues with the thesis about the constructivistic nature of Integrali (Integrals), and places its genesis in the framework of surrealism. Considering the absolute synchrony of the volume with the beginning of the surrealism as such, it points out its relevance in the broadest sense.
Keywords: biografije; ekspresionizem; Expressionism; Kosovel, Srečko, 1904-1926; literarne študije; Slovene literature; slovenska književnost; slovenska poezija